Relationship Between Language Preference and Intravenous Thrombolysis Among Acute Ischemic Stroke Patients - Luan Erfe, Betty (J Am Heart Assoc, 2016)
BACKGROUND: Approximately 20% of the US population primarily speaks a language other than English at home. Yet the effect of language preference on treatment of acute ischemic stroke (AIS) patients remains unknown. We aimed to evaluate the influence of language preference on AIS patients’ receipt of intravenous (IV) thrombolysis. METHODS AND RESULTS: We analyzed data from 3894 AIS patients who participated in the American Heart Association “Get With The Guidelines(®)—Stroke” program at our hospital from January 1, 2003 to April 30, 2014. Information included patients’ language in which they preferred to receive medical care. We used descriptive statistics and stepwise logistic regression models to examine associations between patients’ language preference and receipt of IV thrombolysis, adjusting for relevant covariates. A total of 306/3295 (9.3%) AIS patients preferred to speak a non‐English language and represented 25 different languages. Multivariable analyses adjusting for other socioeconomic factors showed that non‐English‐preferring patients were more likely than English‐preferring patients to receive IV thrombolysis (OR=1.64; CI=1.09‐2.48; P=0.02). However, in models that also included age, sex, and initial NIH Stroke Scale, patients’ language preference was no longer significant (OR 1.38; CI=0.88‐2.15; P=0.16), but NIH Stroke Scale was strongly associated with receiving IV thrombolysis (OR=1.15 per point; CI=1.13‐1.16; P<0.0001). CONCLUSIONS: Contrary to our hypothesis, non‐English‐preferring was not associated with lower rates of IV thrombolysis among AIS patients once initial stroke severity was accounted for.